Peisistratos and the Tyranny : A Reappraisal of the Evidence - Sancisi-Weerdenburg, Heleen, (Publications of the Netherlands Institute at Athens ;, 2000)
The period when the tyrants dominated Athens is a very intriguing one. The historiographical evidence is of a late date and often of a puzzling nature. Connections between historiography and the archaeological evidence are not unproblematic. Is the traditional interpretation of the Peisistratids as sponsors of the arts sufficiently documented in our sources? What was the nature of the resistance they met with? What did the Athenian army look like in the second half of the sixth century? What was the level of institutional organisation of the Athenian state in this period? How does the tyranny compare to anthropological theory? These are the questions addressed in this volume by a group of Dutch archaeologists and ancient historians.